Socio-Demographic Predictors of Pain Catastrophizing in Patients with Different Types of Chronic Pain - Asanova, Azize (Psychosomatic Medicine and General Practice, 2025)
Background. Pain catastrophizing is one of the key cognitive–affective mechanisms contributing to the pain chronification and the development of functional disability. However, the role of socio-demographic factors in shaping pain catastrophizing remains insufficiently explored, particularly in the context of etiopathogenetic heterogeneity of chronic pain. Objective. To identify socio-demographic predictors of pain catastrophizing and to evaluate their differential role across various etiopathogenetic types of chronic pain within the biopsychosocial model. Materials and Methods. The study initially included 340 outpatients with chronic pain; 302 patients completed the full research protocol. All patients were stratified into five groups according to etiopathogenetic pain types: primary psychogenic pain; psychophysiological pain; mixed primary psychogenic and psychophysiological pain; secondary mixed pain; and secondary organic pain. Pain catastrophizing was assessed using the Pain Catastrophizing Scale (PCS). Associations between catastrophizing and socio-demographic characteristics were analyzed using logistic and linear regression, Fisher’s exact test, and Cramér’s V coefficient. Results. Clinically significant pain catastrophizing (PCS ≥ 30) was identified in 28.1% of the total sample of patients with chronic pain. Its prevalence varied significantly depending on the type of chronic pain: the highest levels of pain catastrophizing were observed in the primary psychogenic and secondary mixed pain groups, whereas the lowest levels were found in the secondary organic pain group. Pain catastrophizing was associated with selected socio-demographic factors, the effects of which were differentiated depending on the etiopathogenetic type of chronic pain. Higher educational level, subjective dissatisfaction with financial situation, and place of residence (rural setting) were significant factors of catastrophizing both in the overall sample and in specific clinical groups. Age and sex did not exert a universal influence on catastrophizing, except in certain etiopathogenetic groups where specific gender- and social-related effects were identified. Marital status and employment did not demonstrate a general impact on catastrophizing; however, their significance varied depending on the pain type. Conclusions. Pain catastrophizing is a heterogeneous and context-dependent psychological phenomenon that emerges from the interaction between etiopathogenetic pain mechanisms and socio-demographic factors. Social and demographic factors do not function as universal predictors of catastrophizing but rather act as moderators of its expression across different types of chronic pain. The findings support the feasibility of a stratified approach to the assessment of pain catastrophizing and confirm its value as a clinically relevant psychological marker in the formation of different pain types, which is essential for the personalization of therapeutic strategies in patients with chronic pain. Keywords: chronic pain, pain catastrophizing, socio-demographic predictors, markers, associations.